Overview of 71 European community-based initiatives against childhood obesity starting between 2005 and 2011: general characteristics and reported effects - Bemelmans, Wanda Jose Erika (BioMed Central, 2014)
BACKGROUND: Community-based initiatives (CBIs) on childhood obesity are considered a good practice approach against childhood obesity. The European Commission called for an overview of CBIs implemented from 2005–2011. A survey was executed by the National Institute for Public Health and the Environment of the Netherlands, in collaboration with the World Health Organization Regional Office for Europe. The objective of this paper is to provide an overview of the European CBIs, as identified in the survey, presenting their general characteristics, applied strategies (separately for actions targeting the environment and/or directly the children’s behaviour) and the reported effects on weight indicators. METHODS: Potentially eligible CBIs were identified by informants in 27 European Union countries, Iceland, Liechtenstein, Norway, and Switzerland, and through desk research. School based approaches could be included if they complied with criteria related to being ‘community-based’. In total, 278 potential eligible CBIs were identified and of these, 260 projects were approached. For 88 an electronic questionnaire was completed; of these 71 met all criteria. The included projects were reported by 15 countries. RESULTS: 66% of the 71 CBIs implemented actions in more than one setting or throughout the neighbourhood. Most frequently reported environmental actions were professional training (78%), actions for parents (70%), and changing the social (62%) and physical (52%) environment. Most frequently reported educational activities were group education (92%), general educational information (90%), and counselling sessions (58%). The vast majority (96%) implemented both environmental and individual strategies and about half of the CBIs reported a public-private partnership. Eight CBIs provided evidence supporting positive effects on weight indicators and/or overweight prevalence in a general population of children (aged 6 to 12 yrs), and one CBI did not support this. Two of those CBIs were also conducted among adolescents (aged 12 to 16,5 yrs), but showed no effect in this age-group. CONCLUSIONS: Despite diversity of included CBIs, common characteristics were the application of integrated actions at a local level, aimed at changing the environment and the children’s behaviour directly. Evidence supporting effectiveness on weight indicators is available, although the design and conduct of most of these studies were suboptimal (i.e. no control group, a small sample size, not random). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2458-14-758) contains supplementary material, which is available to authorized users.